THE ROLE OF TBM SUKAMULYA CERDAS MANAGERS IN INCREASING LITERACY IN THE COMMUNITY ENVIRONMENT THROUGH THE LITERACY CAMPAIG PROGRAM - Rini Rahayu (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
ABSTRACT The background of the researchers conducting this research is to increase community literacy, but literacy is meant not only that people can read, write and count, but the public can know all important aspects other than education as an investment for the future of them as well as to advance the nation and the State we are in accordance with the times at this time. The current achievement that has been obtained by the Indonesian State is one proof that Indonesia has gone through a literacy crisis in this case literacy. The research objective is to find out how the role of the TBM Sukamulya Cerdas manager in increasing literacy in the community through the village literacy program. Theories used in this research are TBM theory, Literacy theory and literacy village theory. Researchers used interview and observation techniques with qualitative descriptive methods to obtain information from informants. The sample in this study was a TBM manager and three representatives of TBM Sukamulya Cerdas visitors. The results of research at TBM Sukamulya is the role of TBM Sukamulya Cerdas in increasing literacy in the community through the village literacy program that has run well seen from the achievement of increasing the ability of literacy in the surrounding communities through the role of managers who provide programs that are in accordance with the concept of literacy villages. The role of TBM managers is crucial in improving community capacity in literacy.ABSTRACT The background of the researchers conducting this research is to increase community literacy, but literacy is meant not only that people can read, write and count, but the public can know all important aspects other than education as an investment for the future of them as well as to advance the nation and the State we are in accordance with the times at this time. The current achievement that has been obtained by the Indonesian State is one proof that Indonesia has gone through a literacy crisis in this case literacy. The research objective is to find out how the role of the TBM Sukamulya Cerdas manager in increasing literacy in the community through the village literacy program. Theories used in this research are TBM theory, Literacy theory and literacy village theory. Researchers used interview and observation techniques with qualitative descriptive methods to obtain information from informants. The sample in this study was a TBM manager and three representatives of TBM Sukamulya Cerdas visitors. The results of research at TBM Sukamulya is the role of TBM Sukamulya Cerdas in increasing literacy in the community through the village literacy program that has run well seen from the achievement of increasing the ability of literacy in the surrounding communities through the role of managers who provide programs that are in accordance with the concept of literacy villages. The role of TBM managers is crucial in improving community capacity in literacy.